Patterns of service utilisation within Australian hepatology clinics: high prevalence of advanced liver disease. Issue 4 (7th April 2016) - El‐Atem, N. A.; Wojcik, K.; Horsfall, L.; Irvine, K. M.; Johnson, T.; McPhail, S. M.; Powell, E. E.
Abstract : Background: Liver diseases in Australia are estimated to affect 6 million people with a societal cost of 51 billion annually. Information about utilisation of specialist hepatology care is critical in informing policy makers about the requirements for delivery of hepatology‐related healthcare. Aims: This study examined the aetiology and severity of liver disease seen in a tertiary hospital hepatology clinic, as well as the resource utilisation patterns. Methods: A longitudinal cohort study included consecutive patients booked in hepatology outpatient clinics during a 3‐month period. Subsequent outpatient appointments for these patients over the following 12 months were then recorded. Results: During the initial 3‐month period, 1471 appointments were scheduled with a hepatologist, 1136 of which were attended. Twenty‐one per cent of patients were 'new cases'. Hepatitis B virus (HBV) was the most common disease aetiology for new cases (37%). Advanced disease at presentation varied between aetiology; only 5% of HBV cases had advanced liver disease at presentation, in contrast with HCV, NAFLD and ALD, in which advanced disease was identified at presentation in 31%, 46% and 72% of cases, respectively. Most patients (83%) attended multiple hepatology appointments, and a range of referral patterns for procedures, investigations and other specialty assessments were observed. Conclusions: There is a high prevalence of HBV in new case referrals. Patients with HCV infection, NAFLD and ALD have a high prevalence of advanced liver disease at referral, requiring ongoing surveillance for development of decompensated liver disease and liver cancer. These findings that describe the patterns of health service utilisation among patients with liver disease provide useful information for planning sustainable health service provision for this clinical population.